Unconventional monetary policy, fiscal side effects and euro area (im)balances - Michael Hachula; Michele Piffer; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We study the macroeconomic effects of unconventional monetary policy in the euro area using structural vector autoregressions, identified with an external instrument. The instrument is the common unexpected variation in euro area sovereign spreads for different maturities on policy announcement days. We first show that expansionary monetary surprises are effective at lowering public and private interest rates and increasing economic activity, consumer prices, and inflation expectations. We also find, however, that the shocks lead to a rise in primary public expenditures, a divergence of consumer prices within the union, and a widening of internal trade balances.
Keywords: E52; E58; E63; 330; central banks; structural VAR with external instruments; fiscal policy; monetary union